PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KUALITAS KERJA KARYAWAN PADA PT KARYA KERINCI SEBLAT CILEUNGSI - BOGOR - Nadiah Nurfauziah; Ninik Anggraini (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the positive and significant impact of the competence variable on employee work quality, to ascertain the positive and significant effect of the compensation variable on employee work quality, and to examine the simultaneous positive and significant effect of competence and compensation on employee work quality at PT Karya Kerinci Seblat Cileungsi - Bogor. The sample used was a saturated sampling technique involving 95 employees. Data collection was conducted through primary and secondary data. The method used is quantitative with an associative approach. The results of the study indicate that: (1) partially, competence has a positive effect on employee work quality, which can be evidenced by the linear regression test yielding the regression equation Y = 19.017 + 0.384X1, thus concluding that the constant value is 19.017. The t-test shows a calculated value of 5.340 and a table value of 1.986 at the 5% significance level, hence 5.340 > 1.986 with a significance level of 0.000 < 0.05. (2) Partially, compensation also has a positive effect on employee work quality, supported by the linear regression test yielding the regression equation Y = 19.017 + 0.220X2, leading to a constant value of 19.017. The t-test shows a calculated value of 2.852 and a table value of 1.986 at the 5% significance level, so 2.852 > 1.986 with a significance level of 0.005 < 0.05. (3) Simultaneously, there is a positive and significant effect of both competence and compensation on employee work quality, evidenced by the multiple linear regression equation Y = 19.017 + 0.384X1 + 0.220X2, with a coefficient of determination of 66.5%, and a calculated F value of 36.449 > table F value of 3.090 with a significance level of 0.000 < 0.05.